2014
DOI: 10.1007/s10753-014-9895-0
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effect of B-Type Natriuretic Peptide Postconditioning During Myocardial Ischemia–Reperfusion: Involvement of PI3K/Akt Signaling Pathway

Abstract: High mobility group box 1 protein (HMGB1) plays an important role in myocardial ischemia-reperfusion (I/R) injury. B-type natriuretic peptide (BNP) postconditioning has been reported to reduce myocardial I/R injury. The present study investigated whether postconditioning of BNP could reduce myocardial I/R injury by inhibiting HMGB1 expression and the potential mechanisms in rats. The left anterior descending coronary arteries of rats were occluded to induce ischemia for 30 min and reopened to imitate reperfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 23 publications
5
41
0
Order By: Relevance
“…In the later stages of IRI, the role of macrophages transforms into an anti-inflammatory one, as they repair renal damage (Duffield, 2011;Huen and Cantley, 2015). It has been previously shown that BNP can inhibit cardiac inflammation induced by IRI (Hu et al, 2014). We also observed macrophage infiltration at an early stage of IRI (24 h after reperfusion) and noticed a pro-inflammatory phenotype of the macrophages (Kinsey, 2014;Huen and Cantley, 2015).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In the later stages of IRI, the role of macrophages transforms into an anti-inflammatory one, as they repair renal damage (Duffield, 2011;Huen and Cantley, 2015). It has been previously shown that BNP can inhibit cardiac inflammation induced by IRI (Hu et al, 2014). We also observed macrophage infiltration at an early stage of IRI (24 h after reperfusion) and noticed a pro-inflammatory phenotype of the macrophages (Kinsey, 2014;Huen and Cantley, 2015).…”
Section: Discussionsupporting
confidence: 65%
“…BNP belongs to the natriuretic peptide family and is synthesized and secreted mainly by cardiac myocytes, where it is used as a hemodynamic parameter that can reflect left ventricular dysfunction and decompensated heart failure (Jaffe et al, 2006). Many studies have demonstrated that BNP functions as an anti-inflammatory, antioxidant and anti-apoptotic factor that can protect the heart from IRI (Hu et al, 2014). However, whether BNP can also protect the kidney from damage is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For patients with acute or chronic coronary artery diseases, both IFN-γ and TNF-α are significantly increased. Intervention of TNF-α may improve myocardial ischemia, with the time of intervention being either before reperfusion or at the beginning of reperfusion (31). Intervention at the beginning of reperfusion was discovered to have an influential role in the recovery of myocardium (31).…”
Section: Discussionmentioning
confidence: 99%
“…Intervention of TNF-α may improve myocardial ischemia, with the time of intervention being either before reperfusion or at the beginning of reperfusion (31). Intervention at the beginning of reperfusion was discovered to have an influential role in the recovery of myocardium (31). It is therefore feasible to consider the inflammatory factor TNF-α, as a useful treatment at the beginning of reperfusion (29).…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports that have been published regarding anti-inflammatory and anticancer activity of natriuretic peptides [114116]. The NPR-A has been reported to be expressed in various types of cancer, such as lung cancer, ovarian cancer, gastric cancer and prostate cancer [117119].…”
Section: Roles Of Natriuretic Peptides In Metabolic Syndromementioning
confidence: 99%